Insulin reverses impaired alveolar fluid clearance in ARDS by inhibiting LPS-induced autophagy and inflammatory - Wen, Xu-peng; Li, Min; Zhang, Ru-qi; Wan, Qi-quan (Frontiers in Immunology, 2023)
Until now, acute respiratory distress syndrome (ARDS) has been a difficult clinical condition with a high mortality and morbidity rate, and is characterized by a build-up of alveolar fluid and impaired clearance. The underlying mechanism is not yet fully understood and no effective medications available. Autophagy activation is associated with ARDS caused by different pathogenic factors. It represents a new direction of prevention and treatment of ARDS to restrain autophagy to a reasonable level through pharmacological and molecular genetic methods. Na, K-ATPase is the main gradient driver of pulmonary water clearance in ARDS and could be degraded by the autophagy-lysosome pathway to affect its abundance and enzyme activity. As a normal growth hormone in human body, insulin has been widely used in clinical for a long time. To investigate the association of insulin with Na, K-ATPase, autophagy and inflammatory markers in LPS-treated C57BL/6 mice by survival assessment, proteomic analysis, histologic examination, inflammatory cell counting, myeloperoxidase, TNF-α and IL-1β activity analysis etc. This was also verified on mouse alveolar epithelial type Ⅱ (AT Ⅱ) and A549 cells by transmission electron microscopy. We found that insulin restored the expression of Na, K-ATPase, inhibited the activation of autophagy and reduced the release of inflammatory factors caused by alveolar epithelial damage. The regulation mechanism of insulin on Na, K-ATPase by inhibiting autophagy function may provide new drug targets for the treatment of ARDS.